Calculation of the Moments of the Cardinal B-Spline - Udovičić, Zlatko (Sarajevo Journal of Mathematics, 2024)
In this paper we describe five methods for the calculation of the moments equation*Momenti M_n,m=_0^mφ_m(t)t^ndt, nN_0, equation* where weight function φ_m(·) is the cardinal B-spline of order m,mN. 2000 Mathematics Subject Classification. 65D07, 41A15